2022
DOI: 10.3389/jaws.2022.10914
|View full text |Cite
|
Sign up to set email alerts
|

Description of the Current Da Vinci® Training Pathway for Robotic Abdominal Wall Surgery by the European Hernia Society

Abstract: Background: Robot assisted laparoscopic abdominal wall surgery (RAWS) has seen a rapid adoption in recent years. The safe introduction of the robot platform in the treatment of abdominal wall hernias is important to safeguard the patient from harm during the learning curve. The scope of this paper is to describe the current European training curriculum in RAWS.Methods and Analysis: The pathway to competence in RAWS will depend on the robot platform, experience in other abdominal procedures (novice to expert) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…Vierstraete et al describe the current training pathway of abdominal wall reconstruction and ventral hernia repair and found in their experience of posterior component separation that there was a gradual reduction in operative time until the surgical team reached their ‘comfort zone’ at around 20–25 cases. Depending on the frequency with which this procedure is performed, it may take a long period of time for the surgeon to reach that level of experience [ 189 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vierstraete et al describe the current training pathway of abdominal wall reconstruction and ventral hernia repair and found in their experience of posterior component separation that there was a gradual reduction in operative time until the surgical team reached their ‘comfort zone’ at around 20–25 cases. Depending on the frequency with which this procedure is performed, it may take a long period of time for the surgeon to reach that level of experience [ 189 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, abdominal wall surgery has been recognized as a subspecialty by the Unión Européenne des Médecins Spécialistes (UEMS), in collaboration with the European Hernia Society (EHS) [ 15 ] mostly because of a greater awareness of hernia clinical and community implications, complexity of the abdominal wall anatomy, development and description of new procedures and materials for hernia repair. Nowadays, a minimum number of procedures to achieve proficiency in TAPP repair is not well established yet [ 2 , 3 , 10 ] although some groups defend around 50–100 procedures as the minimum number for TAPP learning curve [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the moment, the principal rAWS training pathway is controlled by Intuitive Surgical, Inc® and consists of 5 phases (TR100 and TR200-preclinical, TR300, TR400 and TR500—clinical) including online, video-based, hands-on and live surgery sessions with a proctor [ 27 ]. However, this pathway was designed for generic robotic surgery and it is not rAWS-specific so scientific societies such as the EHS should play the most important role in the design and implementation of these pathways [ 15 ]. In 2023, the Robotic4all Project [ 21 ] showed that a 2-h, non-procedure specific program can be useful for the initial phase of the robotic training pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The repetition of a simulated tasks (under supervision) over a period of time leads to an improvement in results. • Phase IV: Initial case series: the best cases for beginners are primary inguinal hernia and small ventral or umbilical hernias (intraperitoneal underlay mesh-IPUM) • Phase V: Continued development and advanced training: surgeon-led training with a focus on the technical and anatomical aspects of abdominal wall repair procedures (robotic retrorectus ventral hernia repair (RRVHR) [16][17][18][19][20].…”
Section: Specific Training In Robotic Hernia Surgerymentioning
confidence: 99%